Accounting for “the social” in contact tracing applications: The paradox between public health governance and mistrust of government's data use - Yao-Tai Li (SAGE Publishing, 2021)
This essay adopts three accounts (sociological, neoliberal, and cybernetic) of “the social” to get a clearer picture of why there is a barrier faced by the government when implementing contact tracing mobile applications. In Hong Kong's context, the paradox involves declining trust of the government's protection of data privacy and growing concern about data surveillance since the 2019 social unrest I argue that exploring the idea of sociality is valuable in that it re-reconfigures the datafication of pandemic control by revealing different sets of social relations, particularly the asymmetrical power relation between the government and its people. The refusal to download or use the mobile app also shows that the public has a faith in human agency and human resistance in data-saturated cities.